(untitled) (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2026)
The extension of laying hens’ productive lifespan up to 100 weeks is associated with a decline in egg physical quality during the late laying phase due to reduced magnum gland function and impaired liver health, leading to albumen thinning and weakening of the vitelline membrane, which may result in failure to meet SNI 3926:2023 standards. This study aimed to determine the optimal crude protein (CP) level in an isocaloric diet to maintain the stability of egg physical quality in ISA Brown laying hens during the late laying phase. A Completely Randomized Design (CRD) was applied using 100 ISA Brown hens aged 72 weeks, assigned to four dietary protein levels: P1 (16%), P2 (17%), P3 (18%), and P4 (19%) with metabolizable energy of 2650 kcal/kg. Parameters measured included Albumen Index (AI), Haugh Unit (HU), Yolk Index (YI), and eggshell thickness (EST). The results showed that increasing crude protein levels improved AI, HU, and YI, with the highest values observed in P4 (19% CP), resulting in HU (95.96), AI (0.14), and YI (0.47), classifying eggs as Grade I according to SNI 3926:2023. In contrast, a metabolic dip indicating inefficiency was observed at 18% CP (P3), reflected by decreased internal egg quality. Eggshell thickness remained relatively stable across treatments and was categorized as medium shells. In conclusion, a crude protein level of 19% is the most effective formulation for maintaining the stability of egg physical quality in ISA Brown hens during the late laying phase.